On automatic person-in-water detection for marine search and rescue operations - Taipalmaa, Jussi (IEEE, 2025)
In marine search and rescue missions, the objective is to find a missing person in the water. Time is a critical factor in the identification of the missing person, as any delay in locating them can have life-threatening consequences. Autonomous unmanned aerial vehicles (UAVs) possess the potential to help in the search task by providing a bird’s-eye view helping to cover larger areas faster. Therefore, it is very important that UAVs can efficiently and accurately detect persons in the water. This work studies automatic person detection in the water from a UAV. We performed experiments on both lakes and sea near Turku, Finland and captured videos of people in the water from various altitudes and different viewing angles. Our person-in-water detection tests focus on important factors that have not received sufficient attention in prior studies: evaluation metrics and detection thresholds, the impact and use of different bounding box sizes, multi-frame detection and performance in unseen environments. We provide analysis of the suitability of different approaches for the person detection task and we also publish our training and testing data that includes over 72500 frames. To the best of our knowledge, this is the largest publicly available person-in-water detection dataset.